Evaluating the impact of a community health worker (Promotora de Salud) program on attitudes and beliefs regarding atopic dermatitis among Spanish‐speaking Latin‐American caregivers. Issue 2 (17th February 2022) - Joseph, Adrienne K.; Chen, Henry W.; Hassan Youssef, Sara; Limmer, Emily E.; Eifert, Faye; Dominguez, Arturo R.
Abstract: Introduction: Community health workers (CHWs), or promotora de salud, have an important role in healthcare education and advocacy in the Latin American community. We aimed to determine the impact of a promotora de salud program on attitudes and beliefs regarding AD management among Latin American caregivers of pediatric patients with atopic dermatitis. Methods: This is a sub‐study of an ongoing randomized, investigator‐blinded, placebo‐controlled trial. Mann‐Whitney U tests compared questionnaire responses in the standard education group to the promotora group. Results: Caregivers in the promotora group were more likely to state that they knew how to apply wet wraps and use bleach (sodium hypochlorite) baths at 1 month (wet wraps p = .027, bleach baths p = .005) and 3 months (wet wraps p = .005, bleach baths p < .001) demonstrating greater self‐efficacy, defined as an individual's belief in their capacity to execute a certain behavior to achieve a desired outcome, compared with the standard education group. Conclusions: Culturally competent and language concordant educational interventions may improve confidence in utilizing wet wraps and bleach baths among Latin‐American caregivers of children with atopic dermatitis, which may improve AD outcomes in the Latin‐American community.